Seismic Retrofitting of CD Hospital in Srinagar Kashmir (International Journal of Innovative Research in Engineering & Management, 2021)
This concept sets out the mechanisms designed to re-engineer  seismic analysis. This concept is designed to explain the need  for a new self-based trust code to provide a broad range of  constructive behaviours. The concept also aims to feed the  structure to meet the needs of the current principles of landscape  design. The Kashmir region prevails within the Himalayas and  is one of the world's most popular earthquakes prone area. For  the past ten years the Kashmir region has seen a major  earthquake with Magnitudes hit (M 7.2) in 2005 followed by  massive losses and severe economic losses. Complete loss &  death occurred as a result of the collapse of non-structural  structures, many of which occur as stone structures and thus  further the issue. Unfortunately, the potential for earthquakes in  developing countries like ours continues to grow because the key  principles of building earthquake resistance and code guidelines  issued by the BIS are often not adhered to. Definitions are  ignorance, uncertainty of additional costs and will full  negligence. New buildings can easily be made to withstand  earthquakes, however, existing buildings need to be saved,  including re-installation. The concept aims to fully study the  existing structures of life (Health facilities, schools, etc.) in the  Kashmir district and draw scientific and technological  knowledge into structural assessment followed by adequate,  easily accessible, economic reorganization measures. The aim is  to add and build a user-friendly reusable structure, with  completed high-quality Kashmir
Keywords: Seismic analysis; Earthquake; Retrofitting; Rehabilitation